Constitution of the White Earth Nation - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Gerald Vizenor University of New Mexico   ABSTRACT The Constitution of the White Earth Nation was ratified by sworn delegates on April 4, 2009. The Constitution declares a separation from the current federal constitution that consolidated six Anishinaabe or Chippewa reservations in Minnesota. This federal constitutional association has not served the specific interests of the citizens of the White Earth Reservation. The disposition of treaty land, for instance, and the uses of natural resources cannot equitably be decided by any other government or federation of reservations. Forty citizen delegates were appointed to deliberate the appropriate formation of an independent reservation government. In the past two years after three two-day Constitutional Conventions on the White Earth Reservation, Gerald Vizenor was named the principal writer of the new constitution. The Constitution of the White Earth Nation was ratified at the fourth Constitutional Convention. The ratified Constitution will soon be presented to the citizens of the reservation as a referendum.